A Blessing In Disguise - Ifoegbuna, Ifeanyi (Literamed Publications Nigeria Limited, 1996)
Mr James was a wealthy merchant married to a beautiful woman,they had two daughters.But he was secretly having love affairs outside matrimonial home. His teenage daughters were also secretly having affairs without the knowledge of their parents.
Keywords: AIDS; Juvenile Fiction; Realistic